Transnasal humidified rapid‐insufflation ventilatory exchange (THRIVE) for difficult airway management: a trainee perspective. Issue 1 (9th April 2016) - Aravinth, Kavitha; Alder, Rachel; Patel, Anil
Summary: We present the case of an 86‐year‐old female with an epiglottic mass causing airway obstruction. The use of transnasal humidified rapid‐insufflation ventilatory exchange (THRIVE) to provide apnoeic oxygenation enabled the airway to be safely and successfully managed by an anaesthetic trainee, enhancing their educational experience in difficult airway management.